Relevansi Qawā‘id Fiqhiyyah dalam Menyelesaikan Problematika Hukum Islam di Era Modern: Studi Pendekatan Normatif terhadap Isu Sosial dan Teknologi - Muhammad Iqbal Hanafi Nasution; Muhammad Amar Adly; Heri Firmansyah (Yayasan Dar Arrisyah Indonesia, 2025)
This study discusses the implementation of Qawā‘id Fiqhiyyah (Islamic legal maxims) in addressing and resolving increasingly complex contemporary issues in line with the advancement of time, particularly in the social, economic, and technological domains. Qawā‘id Fiqhiyyah serve as foundational principles in Islamic law that are universal and flexible, enabling them to be applied in response to new problems not explicitly regulated in the scriptural sources (nash). Maxims such as al-‘ādah muḥakkamah (custom is authoritative), al-maṣlaḥah al-mursalah (unrestricted public interest), al-ḍarar yuzāl (harm must be eliminated), and al-mashaqqah tajlib al-taysīr (hardship begets ease) form essential foundations for formulating contextual and beneficial Islamic legal solutions. This research is normative juridical in nature, using a statute approach. Data were obtained from primary legal sources such as the Qur’an, Hadith, and classical texts on uṣūl al-fiqh and qawā‘id fiqhiyyah, supported by secondary and tertiary legal materials. The data analysis technique used is qualitative, with a descriptive-analytical approach. The results of the study indicate that Qawā‘id Fiqhiyyah are capable of serving as adaptive guidelines in establishing Islamic legal rulings on modern phenomena such as digital transactions, sharia-compliant fintech, and contemporary social issues. These maxims provide both theoretical and practical foundations for scholars and academics to perform legal ijtihad, ensuring that Islamic law remains relevant and solution-oriented across eras